Hepatitis C Elimination During a Global Pandemic: A Case Study of Resilience in Action. (July 2022) - Facente, Shelley N.; Grinstein, Rachel; Broussard, Janessa; Shost, Jessica; Azari, Soraya; Siruno, Jennifer; Jimenez, Jose A.; Luetkemeyer, Anne F.; Burk, Katie
Until the COVID-19 pandemic, San Francisco's hepatitis C virus (HCV) elimination initiative, End Hep C SF, was expanding and refining HCV testing and treatment strategies citywide, making progress toward local HCV elimination goals. Although a shelter-in-place health order issued in March 2020 categorized HCV testing as an "essential service, " most HCV testing and treatment immediately stopped until COVID-19–safe protocols could be implemented. During the 14 months of pandemic-related organizational closures, End Hep C SF transitioned to a 100% virtual model, maintaining regularly scheduled meetings. Community-based HCV antibody testing decreased 80% from February to April 2020, and HCV treatment initiation also decreased, although both services started to rebound in mid-to-late 2020, partially as a result of End Hep C SF collaborations. End Hep C SF service providers, clinicians, and advocates reported that the continuous communication and common agenda of End Hep C SF—2 principles of the collective impact initiative—served as a familiar touchpoint and helpful source of information during this isolating and uncertain time. Ultimately, End Hep C SF allowed us to continue HCV elimination strategies through 6 lessons learned: maintaining HCV treatment access through telehealth and mobile services; leveraging research studies that provided HCV testing and treatment; offering HCV screening and linkage to care in tandem with COVID-19–related initiatives; being flexible and inventive, such as administering HCV treatment to residents of shelter-in-place hotels; establishing a data dashboard to track HCV testing and treatment; and relying on partnerships to solve problems and avoid burnout.